Proceedings of the 20th International Conference on Fluidized Bed Combustion - Yue, Guangxi; Zhang, Hai.; Zhao, Changsui; Luo, Zhongyang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The Proceedings of the 20th International Conference on Fluidized Bed Combustion collects 9 plenary lectures and 175 peer-reviewed technical papers presented in the conference held in Xi'an, China in May, 2009. It covers the latest fundamental research results, as well as the application experience from pilot plants, demonstrations and industrial units regarding to the fluidized bed combustion (FBC) science and technology. The main subjects include the AFBCs, CFBs, fluid dynamics, heat transfer, chemical reaction, biomass and sustainable fuels, environmental, gasification, operations, mathematical modeling, numerical simulation and controls related to the FBC technologies and facilities. It also includes state-of-the-art fluidized bed combustion technology development in the supercritical circulating fluidized bed boilers, fluidized bed oxy-fuel combustion, and chemical looping, etc. The book serves as an ideal reference for researchers, engineers, academia and graduate students, plant operators, boiler manufacturers, component suppliers, and technical managers who work on fluidized bed combustion technology development and application. Guangxi Yue is a professor at the Department of Thermal Engineering, Tsinghua University. Hai Zhang is an associate professor at the Department of Thermal Engineering, Tsinghua University. Changsui Zhao is a professor at the School of Energy and Environment, Southeast University. Zhongyang Luo is a professor at the Institute of Thermal Power Engineering, Zhejiang University.
Keynotes -- CFB Boiler Technology, Operation and Design -- Fundamental Research on Fluidization and Fludized Combustion -- CO2 Capture and Chemical Looping -- Gasification -- Modling and Simulation -- Environmentals and Pollution Control -- Sustainable Fuels-Combustion and New Concept.
Keywords: Chemistry; Chemical engineering; Mechanical engineering; Industrial engineering; Electric engineering; Biotechnology; Chemistry; Industrial Chemistry/Chemical Engineering; Industrial and Production Engineering; Mechanical Engineering; Energy Technology; Environmental Engineering/Biotechnology.